The coordination chemistry of the neutral tris-2-pyridyl silicon ligand [PhSi(6-Me-2-py)3] - Plajer, Alex; Enders, Markus (Dalton transactions, 2018)
Difficulties in the preparation of neutral ligands of the type [RSi(2-py)3] (where 2-py is an unfunctionalised 2-pyridyl ring unit) have thwarted efforts to expand the coordination chemistry of ligands of this type. However, simply switching the pyridyl substituents to 6-methyl-pyridyl groups (6-Me-2-py) in the current paper has allowed smooth, high-yielding access to the [PhSi(6-Me-2-py)3] ligand (1), and the first exploration of its coordination chemistry with transition metals. The synthesis, single-crystal X-ray structures and solution dynamics of the new complexes [{PhSi(6-Me-2-py)3}CuCH3CN][PF6], [{PhSi(6-Me-2-py)3}CuCH3CN][CuCl2], [{PhSi(6-Me-2-py)3}FeCl2], [{PhSi(6-Me-2-py)3}Mo(CO)3] and [{PhSi(6-Me-2-py)3}CoCl2] are reported. The paramagnetic Fe2+ and Co2+ complexes show strongly shifted NMR resonances for the coordinated pyridyl units due to large Fermi-contact shifts. However, magnetic anisotropy also leads to considerable pseudo-contact shifts so that both contributions have to be included in the paramagnetic NMR analysis.
Im Titel ist die "3" hinter der Formel tiefgestellt
Gesehen am 23.04.2020